2011
DOI: 10.1016/j.molcel.2011.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Genetic Screen for AMPKα2 Substrates Uncovers a Network of Proteins Involved in Mitosis

Abstract: SUMMARY The energy-sensing AMP-activated protein kinase (AMPK) is activated by low nutrient levels. Functions of AMPK, other than its role in cellular metabolism, are just beginning to emerge. Here we use a chemical genetics screen to identify direct substrates of AMPK in human cells. We find that AMPK phosphorylates 28 previously unidentified substrates, several of which are involved in mitosis and cytokinesis. We identify the residues phosphorylated by AMPK in vivo in several substrates, including protein ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
264
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(282 citation statements)
references
References 56 publications
18
264
0
Order By: Relevance
“…For screening purposes, this should reduce the number of false positives. In vivo labeling techniques have recently been used to successfully identify novel substrates of Erk2 and AMPK, 28,30 giving us confidence in identifying PERK substrates in a similar fashion. Such a screen would provide significant information for understanding PERK signaling -/-cells expressing either PeRK WT or M886A were permeabilized, then incubated with thapsigargin and N 6 -furfuryl ATPγs for substrate labeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For screening purposes, this should reduce the number of false positives. In vivo labeling techniques have recently been used to successfully identify novel substrates of Erk2 and AMPK, 28,30 giving us confidence in identifying PERK substrates in a similar fashion. Such a screen would provide significant information for understanding PERK signaling -/-cells expressing either PeRK WT or M886A were permeabilized, then incubated with thapsigargin and N 6 -furfuryl ATPγs for substrate labeling.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31] With this approach, the analog-sensitive kinase uses N 6 -alkylated ATPγS to transfer a thiophosphoryl group to its substrates. The bulky group again confers specificity for the analog-sensitive kinase, and the thiophosphoryl group acts as a label for distinguishing direct substrates from all other phosphorylated proteins in the cell.…”
Section: Perk M886a Can Utilize Bulky Atp Analogs To Label Substratesmentioning
confidence: 99%
“…Threonine 172 -phosphorylated AMPKα transiently associates with several mitotic structures, including centrosomes, spindle poles, the central spindle midzone and the midbody throughout all of the mitotic stages and cytokinesis; 4,5 other studies have further identified a network of proteins involved in mitosis that are substrates of AMPK. 6 Indeed, it has been unambiguously confirmed that threonine 172 -phosphorylated AMPKα localizes to the mitotic spindle poles and increases when cells enter mitosis; 7 the mitotic AMPK activity appears to be essential for normal spindle orientation, and when it is defective, mitosis does not proceed efficiently. In this scenario, we envisioned that the mitosis-associated phosphorylated status of ACACA, a downstream target of AMPK, could also be explained in terms of a previously unrecognized ability of phospho-ACACA to directly associate with the mitotic/cytokinetic apparatus during cell division.…”
mentioning
confidence: 96%
“…Activated AMPK phosphorylates many targets involved in the regulation of glucose metabolism: 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (PFKFB3), glycogen synthase-1 (GYS1), glutamine:fructose-6-phosphate amidotransferase (GFAT1), TBC1D1; lipid metabolism: acetyl-CoA Carboxylase-1 and -2 (ACC1 and ACC2), 3-hydroxy-3-methylglutaryl-CoA reductase (HMGR), PLD1; polarity: cytoplasmic linker protein-170 (CLIP170), golgi-specific brefeldin A-resistance guanine nucleotide exchange factor 1 (GBF1), kinesin light chain-2 (KLC2); transcription: (PGC1, sterol regulatory elementbinding protein-1 (SREBP1), FoxOs, Histone-2B, p300 and HDAC4,5,6; and mitosis: protein phosphatase-1 regulatory subunit 12C (PPP1R12C), p21-activated protein kinase (PAK2) [4,39]. AMPK also contributes to mitochondrial function stimulating mitochondrial biogenesis via phosphorylation of PGC1 co-activator and regulating expression of mitochondrial genes [4].…”
Section: Ampkmentioning
confidence: 99%